The Auditor-Firm Conflict: An Analysis Using Concepts of Exchange Theory. - Nichols, Donald R.; Price, Kenneth H. (The Accounting Review, 1976)
Abstract The auditor's real and perceived independence and autonomy in the performance of the attest function seems universally accepted as a desirable attribute. This study utilizes interpersonal exchange theory to consider in detail some of the factors which may affect the relative power of the auditor to maintain independence in an auditor-firm conflict situation. The term "auditor" refers to a professional accountant who is hired by a company to perform an audit and render an opinion on statements to be provided for a third party. The specific conflict situation occurs when the auditor and firm do not agree on some aspect of the performance of the attest function. Under these circumstances, the firm may attempt to influence the manner in which the attest function is conducted. The firm, in attempting to influence the performance of the attest function, may pressure the auditor to take an action that violates acceptable auditing standards, including the rendering of an inappropriate opinion. Compliance with the firm's demands may lead to violations of professional standards which the auditor wishes to avoid. Failure to comply with the firm's demands may result in sanctions by the firm, including the possibility of termination of the engagement. The equalization of power between the auditor and the firm, resulting in a symmetrical power relationship, could lead to mutual accommodation.